2015
DOI: 10.1186/1472-6831-15-5
|View full text |Cite
|
Sign up to set email alerts
|

Survival of dental implants in patients with oral cancer treated by surgery and radiotherapy: a retrospective study

Abstract: BackgroundThe aim of this retrospective study was to evaluate the survival of dental implants placed after ablative surgery, in patients affected by oral cancer treated with or without radiotherapy.MethodsWe collected data for 34 subjects (22 females, 12 males; mean age: 51 ± 19) with malignant oral tumors who had been treated with ablative surgery and received dental implant rehabilitation between 2007 and 2012. Postoperative radiation therapy (less than 50 Gy) was delivered before implant placement in 12 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
2
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 24 publications
0
73
2
11
Order By: Relevance
“…Seventeen studies were identified which met the inclusion and exclusion criteria (Table ) (Arcuri, Fridrich, Funk, Tabor & LaVelle, ; Bodard et al., ; Buddula et al., ; Cuesta‐Gil et al., ; Eckert, Desjardins, Keller & Tolman, ; Ernst et al., ; Fenlon et al., ; Gander, Studer, Studer, Gratz & Bredell, ; Heberer, Kilic, Hossamo, Raguse & Nelson, ; Hessling et al., ; Korfage et al., ; Linsen, Martini & Stark, ; Mancha de la Plata et al., ; Mericske‐Stern, Perren & Raveh, ; Pompa et al., ; Sammartino, Marenzi, Cioffi, Tete & Mortellaro, ). Most of the studies reported on implants placed after radiotherapy (Arcuri et al., ; Bodard et al., ; Ernst et al., ; Gander et al., ; Heberer et al., ; Hessling et al., ; Korfage et al., ; Linsen et al., ; Mancha de la Plata et al., ; Pompa et al., ; Sammartino et al., ). Only two studies also included patients with implants placed prior to radiotherapy (Hessling et al., ; Mericske‐Stern et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies were identified which met the inclusion and exclusion criteria (Table ) (Arcuri, Fridrich, Funk, Tabor & LaVelle, ; Bodard et al., ; Buddula et al., ; Cuesta‐Gil et al., ; Eckert, Desjardins, Keller & Tolman, ; Ernst et al., ; Fenlon et al., ; Gander, Studer, Studer, Gratz & Bredell, ; Heberer, Kilic, Hossamo, Raguse & Nelson, ; Hessling et al., ; Korfage et al., ; Linsen, Martini & Stark, ; Mancha de la Plata et al., ; Mericske‐Stern, Perren & Raveh, ; Pompa et al., ; Sammartino, Marenzi, Cioffi, Tete & Mortellaro, ). Most of the studies reported on implants placed after radiotherapy (Arcuri et al., ; Bodard et al., ; Ernst et al., ; Gander et al., ; Heberer et al., ; Hessling et al., ; Korfage et al., ; Linsen et al., ; Mancha de la Plata et al., ; Pompa et al., ; Sammartino et al., ). Only two studies also included patients with implants placed prior to radiotherapy (Hessling et al., ; Mericske‐Stern et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The radiotherapy performed in patients with cancer may cause progressive fibrosis of blood vessels and soft tissues, leading to a decrease in vascularization and healing capacity. This decrease in vascularization may be related to the lower survival rate of implants placed in patients irradiated in head and neck (14,15). Likewise, the vasoconstriction caused by smoking seems to have a strong relationship with peri-implant bone resorption in smokers (16).…”
Section: Discussionmentioning
confidence: 99%
“…Muitos pacientes com deformidades oculopalpebrais recebem radioterapia após uma cirurgia de câncer. Os protocolos de radioterapia para tumores de cabeça e pescoço geralmente consistem em irradiação nos campos cervicofaciais, com doses totais entre 50 e 70 Gy 19 . Normalmente, essa dose de radiação é administrada em frações de 2 Gy por dia, durante 5 dias por semana, durante um período de 5 a 7 semanas 19 .…”
Section: Discussionunclassified